1993
DOI: 10.1055/s-2006-959993
|View full text |Cite
|
Sign up to set email alerts
|

Artemisinin, Related Sesquiterpenes, and Essential Oil inArtemisia annuaDuring a Vegetation Period in Vietnam

Abstract: In Vietnam, Artemisia annua (Asteraceae) is a popular medicinal plant, indicated to relieve fever and to stop malarial attacks (1). The plant's active principle, artemisinin, is currently being developed to a registrated antimalarial drug, requiring plants with a high artemisinin content (2). We followed the development of the artemisinin content (HPLC) in A. annua plants and of the biosynthetically related sesquiterpenes arteannuic acid, arteannuin B, and artemisitene (GC), during a vegetation period in Vietn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 0 publications
2
24
0
Order By: Relevance
“…The terpenoid metabolite profiles showed that synthesis and accumulation of terpenoids changed dynamically from VGS to FBS in the two A. annua genotypes. The content of terpenoids compounds reached the highest levels at VGS, decreased at PFBS; however, the content of artemisinin reached the highest level at PFBS, and decreased at FBS, which was consistent with the report of Woerdenbag et al (Woerdenbag et al 1994). Interestingly, the content changes of artemisinic acid and dihydroartemisinic acid exhibited similar dynamics, and their contents decreased rapidly at PFBS.…”
Section: Metabolic Profiling Investigation Of a Annua At Different Ssupporting
confidence: 90%
“…The terpenoid metabolite profiles showed that synthesis and accumulation of terpenoids changed dynamically from VGS to FBS in the two A. annua genotypes. The content of terpenoids compounds reached the highest levels at VGS, decreased at PFBS; however, the content of artemisinin reached the highest level at PFBS, and decreased at FBS, which was consistent with the report of Woerdenbag et al (Woerdenbag et al 1994). Interestingly, the content changes of artemisinic acid and dihydroartemisinic acid exhibited similar dynamics, and their contents decreased rapidly at PFBS.…”
Section: Metabolic Profiling Investigation Of a Annua At Different Ssupporting
confidence: 90%
“…Volatile oil containing cineole, α-pinene, camphene, borneol, camphor, germacrene-D, hydroxyl amino isoartemisia ketone (Woerdenbag et al, 1994), sesquiterpene lactones artemisinin, artemisinic acid, arteanniun B, artemisinin derivatives artesunate, trioxanes, artemether artemisinin G and arteether (He et al, 2009;Bhakuni et al, 1990;Wei et al, 1992); phenolic compounds, flavones (Han et al, 2008;Han et al, 2007)…”
Section: A Annuamentioning
confidence: 99%
“…Artemisia individual plants can produce many thousand (~ 10 5 ) of wind dispersed seeds in a flowering season (Goel et al, 2011). The reproductive stage Artemisia plants are a richer resource of essential oil than vegetative stage plants because of higher density of glandular trichomes, which produce and store essential oil, on inflorescence and leaves of plants on which flowering has set in (Woerdenbag et al, 1994;Ferreira and Janick 1995;Tellez et al, 1999;Soetaert et al, 2013). Whereas several Artemisia species, including Artemisia annua, are commercial resource of essential oils, presently A. annua is the only commercial Artemisia resource of the antimalarial terpenoid drug artemisinin.…”
Section: Morphological and Reproductive System Variationmentioning
confidence: 99%